Karst of Gunung Sewu Land Use and Land Covers Dynamics: Spatio-Temporal Analysis - Hilary Reinhart; Rakhmat Dwi Putra; Muhamad Rifki Rafida; Muhammad Adrian Majiid; Nadhine Salsa Maulita (Universitas Muhammadiyah Surakarta, 2022)
A study of karst land use and land cover dynamics is critical for managing karst areas, which provide many pivotal services for people. This study aims to study such dynamics, especially in relation to the karst of Gunung Sewu, due to its development as a new emerging sector. Using a mixed methods approach, the study combines spatial data analysis with qualitative analysis. Spatial analysis was performed to examine the dynamic of the land cover derived from 2013 and 2021 Landsat 8 imagery, analyzed with the Google Earth Engine tool, together with analysis of spatial patterns using Global Moran’s I and LISA. The spatial analysis results were complemented by a qualitative analysis of the environmental history and development trends, as an explanatory method. The land cover analysis reveals a conversion from vegetation to agriculture, while the spatial pattern analysis shows that such conversion has mostly taken place in the northern part of the study area of Wonosari Basin. The environmental history of teak forest exploitation and agriculture is key to understanding current land use related to the emerging tourism sector, which is fundamental to the region. To manage the negative impacts, sustainable land use with a firm policy framework urgently needs to be implemented.